Strategic Framing in Tax Communication: Reconsidering Policy Narratives Through Justice-Based Approaches - Fitriyah, Aidatul; Nasrulloh, Ubaid Fandi (Sinergi International Journal of Economics, 2025)
This study explores the framing effects in tax policy communication and how they influence public perception, compliance behavior, and institutional trust across various political and cultural contexts. Framing refers to the strategic presentation of tax messages, which can significantly shape public understanding and attitudes. A structured narrative review was employed, synthesizing key empirical and theoretical contributions using targeted keyword searches across multiple databases, but without formal coding protocols as in a systematic review. Key search terms included "framing effects," "tax policy communication," "tax compliance," and "public perception of taxes." The review finds that justice-based framing—emphasizing fairness, social benefits, and moral responsibility—generates higher levels of tax compliance and public support. In contrast, framing taxes solely through economic efficiency tends to weaken public engagement. Contextual factors such as political ideology, media framing, and tax literacy strongly influence message reception. International comparisons further reveal that culturally adaptive framing strategies are more effective, particularly in participatory governance contexts. Despite promising findings, the literature lacks longitudinal studies and cross-cultural analysis. These results underscore the importance of developing tax communication strategies that are transparent, emotionally resonant, and tailored to diverse audiences. Policymakers are encouraged to integrate public feedback, expand tax education, and use digital platforms for interactive engagement. This study contributes to the field by identifying framing as pivotal in advancing equitable and sustainable tax systems.